Adoption intensity of a standardized technical system: The higher the better?—Evidence from China - Li, Yu; Hua, Yongjun; Liao, Bing; Yuan, Xiaohao; Zhou, Ziyuan (Frontiers in Environmental Science, 2022)
Under contract farming, companies usually develop compulsory standardized technical systems for farmers in developing economies. However, in actual production, farmers often have differences in adoption intensity. Using data from 384 households and multinomial endogenous treatment effect regression, this study analyzes factors affecting the adoption intensity of farmers regarding standardized technical systems and estimates the impacts of adoption intensity of the standardized technical systems on household incomes in Chongqing, China. We adapt a multinomial endogenous treatment effect regression framework to correct for selection bias and endogeneity originating from both observed and unobserved heterogeneity. The results show that some factors could significantly affect the adoption intensity, such as farmers, satisfaction with technicians, perception of technology, attitude toward risks of adopting technologies, number of technical trainings, the proportion of leased land, and distances to townships and technology extension stations. Different from current perspectives, the results also indicate that the highest adoption intensity of farmers regarding standardized technical systems does not bring the greatest benefits. Based on the characteristics of a plot, medium adoption intensity has a significant effect on quality improvements and income growth. The conclusion of this study provides an empirical basis for the formulation and evaluation of policies for farmers that apply standardized technology systems in developing countries.